Dermoscopy of Infectious Dermatoses (Infectiouscopy) in Skin of Color-A Systematic Review by the International Dermoscopy Society "Imaging in Skin of Color" Task Force - Payal Chauhan; Biswanath Behera; Delaney D Ding; Aimilios Lallas; Soumil Khare; Nkechi Anne Enechukwu; Martyna Sławińska; Bengu Nisa Akay; Balachandra S Ankad; Yasmeen J Bhat; Abhijeet Kumar Jha; Feroze Kaliyadan; et al. (Mattioli1885, 2023)
Dermoscopy has been showed to facilitate the non-invasive recognition of several infectious disorders (infectiouscopy) thanks to the detection of peculiar clues. Although most of the knowledge on this topic comes from studies involving light-skinned patients, there is growing evidence about its use also in dark phototypes. This systematic literature review summarizes published data on dermoscopy of parasitic, bacterial, viral and fungal dermatoses (dermoscopic findings, used setting, pathological correlation, and level of evidence of studies) and provides a homogeneous terminology of reported dermoscopic features according to a standardized methodology. A total of 66 papers addressing 41 different dermatoses (14 bacterial, 5 viral, 11 fungal infections, and 11 parasitoses/bites and stings) and involving a total of 1096 instances were included in the analysis. The majority of them displayed a level of evidence of V (44 single case reports and 21 case series), with only 1 study showing a level of evidence of IV (case-control analysis). Moreover, our analysis also highlighted a high variability in the terminology used in the retrieved studies. Thus, although promising, further studies designed according to a systematic and standardized approach are needed for better characterization of dermoscopy of infectious skin infections.